Dampak Deraan Kekeringan p ada Fase Inisiasi Bunga, Fase Berbunga dan Fase Pembentukan Polong t erhadap Pembentukan Bunga dan Buah p ada Empat Varietas Vigna radiata - Mangadas Lumban Gaol; Maria Longa Ruma; Hery Leo Sianturi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2009)
One of the greatest affected factors toward the growth of V. radiata is considered as the availability of water. Obviously, less production of V. radiata is due to short water supply. This research shows that flower initiation, flowering and fruiting to reproduction of four V. radiata varieties (Belu, Kenari, Perkutut and Murai), affected by drought are taken under this investigation. Based on numbers of initiated pod flowers and pods being produced, the most sensitive reproduction stages to drought in Belu variety were flower initiation and flowering, Kenari variety were flowering, Murai variety were flowering and fruiting, and Perkutut variety in all reproduction stages posses relatively similar level of sensitivity to drought. Generally, number of flowers initiated pods and the number of pods produced were higher in Kenari and Murai varieties compared to those on Perkutut and Belu. Based on numbers of flowers initiated pods and numbers of pods production, drought at flower initiation and flowering stage were more highly affected on Belu and Perkutut varieties compared to that of Kenari and Murai. Droughts on fruiting stage are highly affected on Perkutut varieties as well compared to other varieties. Therefore, based on plants production and their tolerance to drought, the best plants to be cultivated are Kenari and Murai.